Pengaruh Produk Domestik Regional Bruto (PDRB), Suku Bunga Tabungan dan Inflasi Terhadap Simpanan Masyarakat di Bank Umum Provinsi Bali - I Wayan Yudiana; Gede Aryawan; I Gusti Ayu Athina Wulandari (Warmadewa Economic Development Journal (WEDJ), 2019)
Public savings in Commercial Banks can be a source of funding for the business when channeled back in the form of loans, so that it can encourage the growth of the real sector that has a positive impact on economic growth. The purpose of this research is to know the effect of gross regional domestic products, savings interest rate and inflation to public savings in the commercial bank of the Province of Bali simultaneously and partially. The data used is time period data 2013 until 2017. The research method used in this research is a quantitative method, while the analysis technique used is multiple linear regression analysis. The results of the analysis of this research state that simultaneously gross regional domestic products, savings interest rate and inflation have a positive and significant effect to public savings. Partially, gross regional domestic products have a positive and significant effect to public savings, while savings interest rate and inflation does not have a significant effect to public savings.